Coefficient Bounds for a New Subclasses of Bi-Univalent Functions Associated with Horadam Polynomials - Al-Ziadi, Najah Ali Jiben (JOURNAL OF ADVANCES IN MATHEMATICS, 2021)
this work we present and investigate three new subclasses of the function class of bi-univalent functions in the open unit disk defined by means of the Horadam polynomials. Furthermore, for functions in each of the subclasses introduced here, we obtain upper bounds for the initial coefficients and . Also, we debate Fekete-Szegӧ inequality for functions belongs to these subclasses.